The impact of the level and distribution of methyl-esters of pectins on TLR2-1 dependent anti-inflammatory responses. (1st January 2021) - Beukema, M.; Jermendi, É.; van den Berg, M.A.; Faas, M.M.; Schols, H.A.; de Vos, P.
Highlights: Homogalacturonan pectins mainly inhibit TLR2-1. Pectins with a low DM or intermediate DM with a high DB inhibited TLR2-1 strongest. TLR2 bound strongest to pectins with a low DM or an intermediate DM with a high DB. TLR2-1 inhibiting pectins also inhibited IL-6 secretion from macrophages. Abstract: Pectins have anti-inflammatory effects via Toll-like receptor (TLR) inhibition in a degree of methyl-esterification-(DM)-dependent manner. However, pectins also vary in distribution of methyl-esters over the galacturonic-acid (GalA) backbone (Degree of Blockiness - DB) and impact of this on anti-inflammatory capacity is unknown. Pectins mainly inhibit TLR2-1 but magnitude depends on both DM and DB. Low DM pectins (DM18/19) with both low (DB86) and high DB (DB94) strongly inhibit TLR2-1. However, pectins with intermediate DM (DM43/DM49) and high DB (DB60), but not with low DB (DB33), inhibit TLR2-1 as strongly as low DM. High DM pectins (DM84/88) with DB71 and DB91 do not inhibit TLR2-1 strongly. Pectin-binding to TLR2 was confirmed by capture-ELISA. In human macrophages, low DM and intermediate DM pectins with high DB inhibited TLR2-1 induced IL-6 secretion. Both high number and blockwise distribution of non-esterified GalA in pectins are responsible for the anti-inflammatory effects via inhibition of TLR2-1.